Generation of two iPSC lines (UGENTi003 and UGENTi004) from patients with intermediate rod-cone dystrophy carrying the c.[-123C>T;701G>A];[806_810del] variants in the RDH12 gene - M. Bouckaert; F. Van Den Broeck; M. Ghazvini; A. Dueñas Rey; H. Lenaerts; A. Dheedene; K. Claes; E. De Baere; B.P. Leroy; J. De Zaeytijd; F. Coppieters (Stem Cell Research)
Biallelic variants in RDH12 are associated with early-onset retinal dystrophy and Leber congenital amaurosis. RDH12 plays a role in the phototransduction cascade by converting all-trans retinal into all-trans retinol in the photoreceptor inner segments. Induced pluripotent stem cells (iPSCs) were generated and fully characterized from two patients that are compound heterozygous for the RDH12 c.[-123C>T;701G>A];[806_810del], p.[(?;Arg234His)];[(Ala269Glyfs*2)] variants. These iPSC lines can be used for differentiation towards retinal models to evaluate disease mechanisms and novel therapies.